„BEFORE WE UNDERSTAND WHAT WE ARE DOING, WE NEED TO KNOW HOW WE THINK” - Dörthe Jakobs (Ochrona Dziedzictwa Kulturowego)
The article deals with an interesting debate following a project that started with the question raised by the press: “Why not overpaint or reconstruct the missing parts of a famous wall painting?” and concluded with a panel discussion that conveyed a better understanding of restoration theories on the part of both the press and the parish. Moreover, part of the project featured an exhibition to communicate the basis of our restoration theories and understanding, whilst requesting a dialogue with the priest and the parish; so, they might communicate their intentions and opportunely discuss theological interpretations with regard to the missing part in the wall-painting, which was important for us in reaching an understanding of the principles behind their ideas.